An experimental investigation on phytoremediation performance of water lettuce (Pistia stratiotes L.) for pollutants removal from paper mill effluent. (9th March 2021) - Singh, Jogendra; Kumar, Vinod; Kumar, Pankaj; Kumar, Piyush; Yadav, Krishna Kumar; Cabral‐Pinto, Marina M. S.; Kamyab, Hesam; Chelliapan, Shreeshivadasan
Abstract: The present study describes the phytoremediation performance of water lettuce ( Pistia stratiotes L.) for physicochemical pollutants elimination from paper mill effluent (PME). For this, pot (glass aquarium) experiments were conducted using 0% (BWW: borewell water), 25%, 50%, 75%, and 100% treatments of PME under natural day/light regime. Results of the experiments showed that the highest removal of pH (10.75%), electrical conductivity (EC: 63.82%), total dissolved solids (TDS: 71.20%) biological oxygen demand (BOD: 85.03%), chemical oxygen demand (COD: 80.46%), total Kjeldahl's nitrogen (TKN: 93.03%), phosphorus (P: 85.56%), sodium (Na: 91.89%), potassium (K: 84.04%), calcium (Ca: 84.75%), and magnesium (Mg: 83.62%), most probable number (MPN: 77.63%), and standard plate count (SPC: 74.43%) was noted in 75% treatment of PME after treatment by P. stratiotes . PCA showed the best vector length for TKN, Na, and Ca. The maximum plant growth parameters including, total fresh biomass (81.30 ± 0.28 g), chlorophyll content (3.67 ± 0.05 mg g −1  f.wt), and relative growth rate (0.0051 gg −1  d −1 ) was also measured in 75% PME treatment after phytoremediation experiments. The findings of this study make useful insight into the biological management of PME through plant‐based pollutant eradication while leftover biomass may be used as a feedstock for low‐cost bioenergy production. Practitioner points: Biological treatment of paper mill effluent using water lettuce is presented. Best reduction of physicochemical and microbiological pollutants was attained in 75% treatment. Maximum production of chlorophyll, plant biomass, and highest growth rate was also observed in 75% treatment. Abstract : Experimental setup for the phytoremediation of paper mill effluent using water lettuce.